Evaluation of Al-C-B4C composites fabricated by powder metallurgy for hardness and wear behaviour. (2021) - Sathish Kumar, G.; Rajaguru, K.; Ramkumar, R.; Ranjithkumar, M.
Abstract: In this work, the aluminium composite with carbon and boron carbide has been developed and evaluated for its hardness, corrosion and wear behaviour. High velocity compaction and sintering was used for making composites. Salt Spray method was used for evaluating the corrosion behaviour of the developed composites. Wear was recorded at constant speed and loading conditions for increasing time. The wear rate and resistance was analysed in comparison with SEM analysis. Hardness has increased with the increase in B4C by 44%. Wear and frictional forces between the surfaces has reduced with the inclusion of B4C. The life of the composite has increased with the inclusion of B4C.